Potensi Pesona Wisata IKN - Lionora, Clarisa Alfa; Janah, Nurul; Fitriana, Yenny Reiza; Giovanni, Axel (ICON Publisher, 2025)
Indonesia in mid-2019 announced plans to move the capital of Indonesia outside the island of Java. The location chosen for the new capital is East Kalimantan Province. Data from the East Kalimantan Provincial Culture and Tourism Office in 2022 shows that East Kalimantan has 664 objects dominated by nature tourism. The relocation of the National Capital (IKN) increases the opportunity for tourism development in East Kalimantan as a buffer zone for IKN. Analysis to determine market share and market growth using the Boston Consulting Group (BCG). The paradigm of this research is quantitative with the aim to identify tourism objects and provide proposed strategy formulations for tourism object managers, especially East Kalimantan. The results of BCG matrix calculation show that in 2022, East Kalimantan has a market growth rate of 67.10% with a market share of 0.0163. These results show that the market growth rate is high, but the market share is low. The BCG matrix for East Kalimantan Province is the question mark quadrant, so it can be said that East Kalimantan requires relatively high development and investment costs to turn the tourism sector in the question mark category into stars and later into cash cows. Strategies that can be applied are increasing market share and maintaining growth, investing in human resources, utilizing technology and digitalization, and developing new advantages. The results of this study provide management implications for owners of tourist attractions in East Kalimantan so that tourism can become an important sector for the economy of East Kalimantan.